Biological butanol production from microalgae-based biodiesel residues by Clostridium acetobutylicum. (May 2015) - Cheng, Hai-Hsuan; Whang, Liang-Ming; Chan, Kun-Chi; Chung, Man-Chien; Wu, Shu-Hsien; Liu, Cheng-Pin; Tien, Shih-Yuan; Chen, Shan-Yuan; Chang, Jo-Shu; Lee, Wen-Jhy
Highlights: Butanol production from microalgae biodiesel residues via ABE fermentation. More than twofold of butanol yield increase with additional butyrate of 18–20 g/L. The highest butanol production of 3.86 g/L was achieved with residues of 300 g/L. The highest butanol yield of 0.13 g/g-carbohydrate was with residues of 100 g/L. One third of carbohydrate from residues cannot be utilized by C. acetobutylicum. Abstract: This study conducted batch experiments to evaluate the potential of butanol production from microalgae biodiesel residues by Clostridium acetobutylicum . The results indicated that with 90 g/L of glucose as the sole substrate the highest butanol yield of 0.2 g/g-glucose was found, but the addition of butyrate significantly enhanced the butanol yield. The highest butanol yield of 0.4 g/g-glucose was found with 60 g/L of glucose and 18 g/L of butyrate. Using microalgae biodiesel residues as substrate, C. acetobutylicum produced 3.86 g/L of butanol and achieved butanol yield of 0.13 g/g-carbohydrate via ABE fermentation, but the results indicated that approximately one third of carbohydrate was not utilized by C. acetobutylicum . Biological butanol production from microalgae biodiesel residues can be possible, but further research on fermentation strategies are required to improve production yield.